«ФІЛОСОФІЯ ПРАВА» ГЕГЕЛЯ: ДОСВІД СУЧАСНОГО ПРОЧИТАННЯ - Бредун, І. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Стаття присвячена «Філософії права» Гегеля. «Філософія права» Гегеля є синтезом йогофілософських і політико-правових досліджень. «Філософія права» належить до класичних творів зполітичної і правової філософії.Ключові слова: філософія права, Гегель, політична філософія, правова філософія.Бредун И. В. «ФИЛОСОФИЯ ПРАВА» ГЕГЕЛЯ: ОПЫТ СОВРЕМЕННОГО ПРОЧТЕНИЯ.Статья посвящена «Философии права» Гегеля. «Философия права» Гегеля является синтезом егофилософских и политико-правовых исследований. «Философия права» принадлежит к классическимработам по политической и правовой философии.Ключевые слова: философия права, Гегель, политическая философия, правовая философия.I.Bredun. HEGEL’S “PHILOSOPHY OF LAW”: THE EXPERIENCE OF CONTEMPORARYREADING.The article tells about Hegel’s “Philosophy of Law”. Hegel’s “Philosophy of Law” is the synthesis of hisphilosophical and political-law researches. “Philosophy of Law” belongs to classical works on political and lawphilosophy.Key words: philosophy of law, Hegel, political philosophy, law philosophy.